Using the new ICD‐MM classification system for attribution of cause of maternal death—a pilot study. (September 2014) - Ameh, CA; Adegoke, A; Pattinson, RC; van den Broek, N
Abstract : Understanding the causes of and factors contributing to maternal deaths is critically important for development of interventions that reduce the global burden of maternal mortality and morbidity. The International Classification of Diseases—Maternal Mortality (ICD‐MM) classification of cause of death during pregnancy, childbirth and the puerperium was applied to data obtained from maternal death reviews (MDR) for 4558 maternal deaths from five countries in sub‐Saharan Africa. None of the data sets identified type of maternal death. Information obtained via MDR is generally sufficient to agree on classification of cause of death to the levels of type and group. The terms 'underlying cause of death' and 'contributing conditions' were used differently in different settings and a specific underlying cause of death was frequently not recorded. Application of ICD‐MM resulted in the reclassification of 3.1% (9/285) of cases to the group 'unanticipated complications of management', previously recorded as obstetric haemorrhage or unknown. An increased number of cases were assigned to the groups pregnancy‐related infection (5.6–10.2%) and pregnancies with abortive outcome (3.4–4.9%) when a clear distinction was made between women who died 'with' HIV/AIDS of obstetric causes (direct maternal death) and AIDS‐related indirect maternal deaths (group 'non‐obstetric complications'). Similarly, anaemia and obstructed labour were more frequently identified as contributing factors than underlying cause of death. It would be helpful if MDR forms could have explicitly stated variables called: type, group and underlying cause of death as well as a dedicated section to the most frequently occurring contributing conditions recognised in that setting.